Legal Study on Legal Mechanisms to Overcome Racism in Indonesia: Based on Law Number 40 of 2008 concerning the Elimination of Racial and Ethnic Discrimination - Afresal, Moch Nouvanp (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
Racism remains a serious and detrimental social phenomenon that continues to affect individuals and society in Indonesia. Despite being a country known for its ethnic diversity, cases of racial discrimination and injustice persist across various sectors such as education, employment, housing, and public services. This research aims to analyze the legal mechanisms established to address racism in Indonesia, with a specific focus on the implementation of Law Number 40 of 2008 concerning the Elimination of Racial and Ethnic Discrimination. This study adopts a normative legal research method, complemented by empirical legal analysis, to evaluate both the substance of the law and its implementation in practice. Through the normative approach, this research examines legal norms, policies, and judicial decisions relevant to combating racism. Simultaneously, the empirical aspect involves evaluating the effectiveness of law enforcement agencies, public awareness efforts, and access to justice for victims of racism. The analysis highlights several key challenges in implementing the law, including limited public understanding of legal protections, inadequate capacity of law enforcement, and insufficient sanctions against perpetrators. The study finds that while Law Number 40 of 2008 provides a solid legal foundation, its enforcement still requires significant improvements. Policy recommendations include strengthening legal sanctions, enhancing institutional capacity, increasing public education campaigns, and promoting active participation from civil society organizations. Moreover, collaboration among government agencies, human rights institutions, and community organizations is essential to ensure the law’s effective implementation and to build a more inclusive society. Ultimately, this research underscores the urgent need for continuous evaluation and refinement of legal frameworks and their enforcement to eradicate racism and uphold human rights in Indonesia.